Community satisfaction index on the quality of academic and non-academic services at Jambi University - Junaidi, Junaidi; Amir, Amri; Syaparuddin, Syaparuddin (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2022)
This study aims to measure the community satisfaction index regarding the academic and non-academic services provided by Jambi University. The data used are sourced from community surveys involving students, alumni, faculty members, and administrative staff who receive services at Jambi University (faculties, institutes, units). The analytical tool used is descriptive statistical analysis. The analysis results show that the community satisfaction index for the quality of services at Jambi University is 76.09, falling within the service quality interval "C," indicating "less good" performance. Based on the assessment aspects, it is observed that out of 11 aspects, 5 are categorized as good (score B), and 6 are categorized as less good (score C). No aspects are categorized as very good (score A). Based on the total CSI scores for each faculty, out of the seven evaluated faculties, three are categorized as good, while the other four are categorized as less good. Of the six service aspects assessed, only the performance of the environmental aspect meets user expectations, with a gap value of 105.00. In other words, the quality performance of the environmental aspect has met and even exceeded user expectations. Conversely, the performance of the other five aspects has not fully met user expectations. The aspect with the lowest performance in meeting user expectations is the process aspect, with a gap value of 98.92